Meningkatkan Eksistensi Perpustakaan melalui Aspirasi Pemustaka - Junaeti, Junaeti; Nuryani, Nani; Asirah, Khusnu (Pustabiblia: Journal of Library and Information Science, 2023)
The challenges for libraries today are enormous. As a growing organization, libraries must keep up with the times and the increasingly diverse information technology to survive and not be eroded by the times. Various efforts need to be made to maintain the library's existence by consistently providing the best service and involving the aspirations of the community served. This research aims to help improve the existence of UIN K.H. Abdurrahman Wahid Library as supporting the tri dharma of higher education. The approach in this research is qualitative with the type of field research. The data collection method was conducted through focus group discussion (FGD). Participants in this FGD are students, lecturers, and academic staff representatives. The results of this study found that several things need to be considered to improve the library's existence, including various aspects, namely policies, services, collections, facilities, literacy activities, cleanliness, and human resources. The contribution of this research is used as a guideline to improve library governance and provide many conveniences to library users so that they feel the library's existence.